Review on Exploring Belongings of Parent Involvement on Student’s Learning Performance (Spandan, 2023)
In general, parental involvement refers to the parents' participation in their children's education with the intention of enhancing both their social and intellectual wellbeing. These include a range of activities, involving helping with and keeping updates on homework at home, participating in school events and parent-teacher conferences, communicating with teachers, volunteering at the school, and working with the community. The study aim to explore a brief preview of parental involvement and the learning condition of their children. To draw a summary of specially selected studies on the parental involvement review of literature from Google Scholar and other databases are important sources as study methodology. So the desk review technique was employed for thematic interpretation of literature. Engagement from parents and student achievement are significantly correlated, according to research findings on the impact of parental involvement on children's academic performance. Students' performance tends to be influenced more when parents are actively involved. Parental involvement with a child's education begins in nursery early on and continues through primary, secondary, and higher education. Nevertheless, as children's grades increases, the possibility of parents staying active in their education subsequently decreases. According to the literature, the theoretical combination of parental involvement and students' academic success in countries that are developing has not received sufficient research attention. As a result, further research is required.